Adaptive capacity of workers depending on working conditions by industry of the republic of kazakhstan - BISAKAJEV S. G.; ABIKENOVA SH. K.; BEKEEVA S. A.; DZHUMAGULOVA N.G.; YESPENBETOVA ZH. KH. (The journal of contemporary issues in business and government, 2020)
The problem of ensuring safe working conditions and maintaining the working capacity of employees of enterprises is important in any economic sector. This is a broad and complex task requiring coordinated joint work of labor protection specialists, hygienists, trade union workers, etc. In Kazakhstan, unfortunately, despite the measures taken, there remains a high proportion of those working in hazardous working conditions, which in some sectors reaches 65-70%. In this regard, it is of interest to study the adaptation process, that is, to increase the body's resistance to external factors, and to control these processes. Purpose: to assess the impact of working conditions on the adaptive potential of the body of workers by comparing hemodynamic parameters (blood pressure, heart rate) and adaptation (adaptive potential of the circulatory system, physical condition index, body mass index), taking into account the working conditions of production personnel at enterprises of construction, mining and manufacturing, transportation and agriculture. Methods. When studying the problems of adaptive potential, a biomedical approach was used, i.e. comparison of indicators of the functional state of the body and the ability to adequately respond to adverse factors of the working environment. The assessment of the adaptive potential of workers was carried out according to a method based on measuring height, body weight, heart rate at rest, systolic and diastolic blood pressure. Results. The adaptive potential of the body of 296 surveyed workers (166 professions, age 31-70 years), most of them are assessed as satisfied (43%), at the same time, there is an unsatisfactory adaptation in 15%, failure of adaptation in 5% of workers. Conclusions: Harmful working conditions lead to a deterioration in the functional state and depletion of the adaptive reserves of the body of workers. In this regard, timely preventive measures are needed to preserve the working capacity of workers. This method can be used as an express method for assessing the functional state of workers.